Juvenile Idiopathic Arthritis With Epstein-Barr Virus-Associated Smooth Muscle Tumor in a 6-Year-Old Girl: A Rare Case Report - Zhijuan Kang; Zhijuan Kang; Juan Xu; Zhihui Li; Zhihui Li (Frontiers Media S.A., 2021)
Herein, we reported a rare case of Epstein-Barr virus-associated smooth muscle tumor (EBV-SMT) combined with juvenile idiopathic arthritis (JIA) in a 6-year old girl without HIV, organ transplantation, or congenital immunodeficiency. The patient suffered from pain in the bilateral hip joints, which drastically affected her physical activity. Consequently, she was diagnosed with JIA (September 2019). She was given methotrexate and methylprednisolone pills via oral route and a subcutaneous injection of Recombinant Human Tumor Necrosis Factor-α Receptor II;lgG Fc Fusion Protein for 4 weeks that successfully relieved the pain. In May 2020, the pain reoccurred and was accompanied by occasional headaches. After extensive pathological examination, the patient was diagnosed with EBV-SMT. The imaging examinations after admission showed multiple lesions in the skull, lungs, and vertebral body. Biopsy of the L2 vertebral body was then performed to clarify the diagnosis. Finally, the in-situ hybridization of the tumor of the lumbar vertebrae suggested a non-HIV/transplantation-related EBV-SMT. Consequently, the patient received surgery without chemotherapy and radiotherapy, after which her conditions improved.